2023
DOI: 10.1111/joim.13724
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic clocks indicate that kidney transplantation and not dialysis mitigate the effects of renal ageing

Ognian Neytchev,
Helen Erlandsson,
Anna Witasp
et al.

Abstract: BackgroundChronic kidney disease (CKD) is an age‐related disease that displays multiple features of accelerated ageing. It is currently unclear whether the two treatment options for end‐stage kidney disease (dialysis and kidney transplantation [KT]) ameliorate the accelerated uremic ageing process.MethodsData on clinical variables and blood DNA methylation (DNAm) from CKD stage G3–G5 patients were used to estimate biological age based on blood biomarkers (phenotypic age [PA], n = 333), skin autofluorescence (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…While this result is very encouraging, there is a caveat: the authors found no significant differences in epigenetic age acceleration between a control group of healthy individuals at baseline and the group patients with kidney transplantation 1 year after their surgery. This raises doubts about the validity of epigenetic clocks, especially since patients with kidney transplantation have a reduced life expectancy relative to controls, as it was acknowledged by the same authors ( Neytchev et al, 2024 ). The inclusion of different epigenetic clocks might partially overcome this issue since some epigenetic clocks have been specially designed to be more sensitive to the occurrence of adverse health effects.…”
Section: Discussionmentioning
confidence: 99%
“…While this result is very encouraging, there is a caveat: the authors found no significant differences in epigenetic age acceleration between a control group of healthy individuals at baseline and the group patients with kidney transplantation 1 year after their surgery. This raises doubts about the validity of epigenetic clocks, especially since patients with kidney transplantation have a reduced life expectancy relative to controls, as it was acknowledged by the same authors ( Neytchev et al, 2024 ). The inclusion of different epigenetic clocks might partially overcome this issue since some epigenetic clocks have been specially designed to be more sensitive to the occurrence of adverse health effects.…”
Section: Discussionmentioning
confidence: 99%
“…Late stage CKD is also associated with increased biological age, as predicted by DNA methylation patterns in blood samples. This increase is reduced upon kidney transplant, but not by dialysis [ 18 ]. Remarkably, renal methylation signatures also accurately reflect the presence of kidney cancer, with the methylome of RCC cells exhibiting a significantly older biological age, a phenomenon seen in a wide range of cancers.…”
Section: Dna Methylation Correlates With Lifespan Healthspan and Ckdmentioning
confidence: 99%
“…Chronic kidney disease is a condition associated with premature biological aging [8], and investigations of DNA methylation biomarkers may be used for prognostic or risk stratification in CKD. A recent study evaluating epigenetic clocks through DNA methylation suggests that end-stage kidney failure patients have an epigenetic age of about 5 years older than their chronological age [9]. In the future, the extent of vascular aging in the toxic uremic milieu needs to replace chronological age as a more accurate measure.…”
mentioning
confidence: 99%